Teachers’ Readiness in Teaching English Based on Curriculum 2013 at Madrasah Tsanawiyah Negeri 1 Kolaka - Reskiawan, Bimas -; idris, henny novianti (ELT Worldwide: Journal of English Language Teaching, 2021)
Successful of curriculum 2013 not only on the accuracy and comprehensive design of curriculum substance, but from the principal leadership at the level of school and leadership of teachers at the level of class.The objectives of this research was to describe the teachers’ readiness in teaching English based on curriculum 2013 at Madrasah Tsanawiyah Negeri 1 Kolaka which viewed from dimension of planning, process, and evaluation. The design of the research was qualitative. When conduct the research, the researcher using two instruments in collecting the data, they are: questionnaire and interview. Subject of this research was all of the English teachers in Madrasah Tsanawiyah Negeri 1 Kolaka. This research was conducted along one week. The result of this research exposed that teachers already taught English subject based on curriculum 2013, which viewed from dimension of teaching planning, the percentage was 87,41%. Teaching process, the percentage was 80,46%. Teaching evaluation, the percentage was 83,52%.